Business Ethics in Progress? - Geer, Hans (Studies in economic ethics and philosophy., 1994)
The volume demonstrates the wide range of current topics within business ethics research, from the theoretical arguments in papers of van Luijk and Petersen, over the descriptive and quantitative studies by Brytting and Bergkvist to the report by De Geer from a case of implementing an ethical code. Of special interest is the section on Central and East European experience with papers by Nemcová, Fekete and Rokitiansky. Together the volume gives a good picture of the state of the art in business ethics.